2021
DOI: 10.21203/rs.3.rs-941620/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potentially Toxic Elemental Contamination in Wainivesi River, Fiji Impacted by Gold-mining Activities using Chemometric Tools and SOM Analysis

Abstract: Potentially toxic elements (PTEs) contamination in Wainivesi River, Fiji triggered by gold-mining activities is a major public health concern deserving attention. However, chemometric approaches and pattern recognition of PTEs in surface water and sediment are yet hardly studied in Pacific Island countries like Fijin urban River. In our study, twenty-four sediment and eight water sampling sites from the Wainivesi River, Fiji were explored to evaluate the spatial pattern, eco-environmental pollution, and source… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
2
4
0
Order By: Relevance
“…The appearance of 10 elements in sediment samples was similar to previous studies that reported that Cr, Mn, Fe, Co, Ni, Cu, Zn, Cd, Pb, As, Hg and Pb around gold mine areas in the Republic of Fiji, China and Papua New Guinea were discovered in high concentrations (Kumar et al, 2022;Tang et al, 2021;Kapia et al, 2016). In particular, the concentrations of Cd, Cr, Cu, Zn and As were 0.33-30, 58-281, 28-100, 118-1013 and 9 mg/kg, respectively.…”
Section: Heavy Metal and Metalloid Concentrations In Water Sediment A...supporting
confidence: 89%
See 1 more Smart Citation
“…The appearance of 10 elements in sediment samples was similar to previous studies that reported that Cr, Mn, Fe, Co, Ni, Cu, Zn, Cd, Pb, As, Hg and Pb around gold mine areas in the Republic of Fiji, China and Papua New Guinea were discovered in high concentrations (Kumar et al, 2022;Tang et al, 2021;Kapia et al, 2016). In particular, the concentrations of Cd, Cr, Cu, Zn and As were 0.33-30, 58-281, 28-100, 118-1013 and 9 mg/kg, respectively.…”
Section: Heavy Metal and Metalloid Concentrations In Water Sediment A...supporting
confidence: 89%
“…The study of heavy metal contamination in water around a gold mine area in Oman was found to be similar to this study in that Zn, Fe, Ni and Mn were higher than the standard (Abdul-Wahab and Marikar, 2012), and Kumar et al (2022) reported that these four elements in the Republic of Fiji (Wainivesi gold mine) were relatively high when compared to the same standard. A study in Thailand (Wang Saphung gold mine) revealed that only Fe and Mn were higher than the standard (Intamat et al, 2016a).…”
Section: Heavy Metal and Metalloid Concentrations In Water Sediment A...supporting
confidence: 81%
“…Recent studies on freshwaters and river basins worldwide have reported that polluted river water by toxic contaminants has worsened over the decades (Islam et al 2015;Siddiqui and Pandey 2019;Kumar et al 2022;Siddique et al 2022). Many studies have revealed that anthropic inputs, including the unplanned urbanization of cities and the development of industries and factories, have increased river water pollution, which degrades surface water quality (Proshad et al 2022;Namngam et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bulk chemical compositions of indoor-dusts can also be correlated to the room’s air-quality ( Praveena et al., 2015 ; Soltani et al., 2015 ) that may also cause health risks. Furthermore, children & juveniles are relatively more vulnerable to environmental heavy metal(oid)s ( Habib et al., 2020 ; Jannat et al., 2022 ; Mohtaderi et al., 2019 ; Islam et al., 2020a , 2020b ; Medunic et al., 2016 ; Kumar et al., 2022 , 2021a , 2021b ; Ahmed et al., 2021 ; Hossain et al., 2022a , 2022b ; Rahman et al., 2022 ; Anik et al., 2022 ). Thus, studies on NORM’s occurrence in the dust of classrooms are of utter importance.…”
Section: Introductionmentioning
confidence: 99%